Analisis Tingkat Pendapatan Pedagang Ikan Asin Di Pantai Malabero Kota Bengkulu - Bahrin Bahrin; Deta Yolanda (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the income level of salted fish traders in the Malabero Beach area of ​​Bengkulu city. The methodology used is descriptive qualitative research by means of in-depth interviews with informants. From the results of the study, it was found that the income of salted fish traders on Malabero Beach was quite high with an average income of Rp. 200,000 to Rp. 300,000 per day, the condition of the household characteristics of salted fish traders was quite good, the average content of the informant's family members was still low. in their productive age to generate income either from selling salted fish or income other than selling salted fish, so that their households are still able to meet their daily needs. They also each have a permanent and livable place to live, it can be said that the average informant is not classified as a poor household. The income of salted fish traders is used to pay for children's education and daily needs, be it food, clothing or shelter. As for the salted fish production process, it is relatively easy and not difficult to do, the process flow starts from buying wet fish to fishermen, then cleaning it, then salting it and then drying it and the fish that are dry enough are selected and ready to be sold.